Thyrotoxic periodic paralysis presenting as acute quadriparesis in a middle-aged male: a case report - Duraikannan, Amarnath; Soni, Pankaj; Anandhasekar, Monikeerthana; Arora, Rishab; Kaur, Manwinder; Sinha, Shaifali (International Journal of Research in Medical Sciences, 2025)
Thyrotoxic periodic paralysis (TPP) is a rare, potentially life-threatening complication of hyperthyroidism characterised by acute flaccid paralysis due to hypokalaemia. We report the case of a 46-year-old man who presented with sudden-onset generalised weakness that progressed to quadriparesis over a few hours. Laboratory investigations revealed severe hypokalaemia (2.6 mmol/l) and thyrotoxicosis (FT3 8.76 pmol/l, FT4 32.71 pmol/l, TSH 0.01 µIU/ml), with elevated thyrotropin receptor antibody (TRAb 12.2 IU/l). Ultrasound revealed diffuse thyroid enlargement with increased vascularity. The patient received intravenous potassium supplementation, propranolol, and carbimazole and completely recovered within 24 hours. He was advised to avoid precipitating factors such as high-carbohydrate meals, alcohol, and strenuous activity, and was referred for definitive management of hyperthyroidism. This case highlights the importance of considering TPP in Asian males presenting with acute flaccid paralysis and hypokalaemia. Early recognition, cautious potassium replacement, and timely initiation of antithyroid therapy are essential to prevent serious complications and ensure complete recovery.